Strategic Flexibility and the Optimality of Pay for Sector Performance - Gopalan, Radhakrishnan; Milbourn, Todd; Song, Fenghua (Review of Financial Studies, 2010)
While standard contract theory suggests that a Chief Executive Officer (CEO) should be paid relative to a benchmark that removes the effects of sector performance, there is evidence that CEO pay is strongly and positively related to such sector performance. In this article, we offer an explanation. We model a CEO charged with selecting the firm’s strategy that determines the firm’s exposure to sector performance. To incentivize the CEO to choose optimally, pay contracts will be positively and sometimes asymmetrically related to sector performance. Consistent with our predictions, the empirical analysis indicates that the observed sensitivity of pay to sector performance is almost fully confined to multisegment firms and is greater in firms that offer greater strategic flexibility to alter sector exposure, for more talented CEOs and for CEOs as compared to their subordinate executives. Our evidence is robust to alternate explanations such as CEO entrenchment.